GAREM1 regulates the PR interval on electrocardiograms - Kim, Hye Ok; Lim, Ji Eun; Kim, Myung Jun; Kang, Ji-One; Kim, Sung-Moon; Nam, Jeong Min; Tak, Jihoon; Konishi, Hiroaki; Nishino, Tasuku; Koh, In Song; Jin, Young-Ho; Baik, Hyung Hwan; et al. (Journal of human genetics, 2018)
PR interval is the period from the onset of P wave to the start of the QRS complex on electrocardiograms. A recent genomewide association study (GWAS) suggested that GAREM1 was linked to the PR interval on electrocardiograms. This study was designed to validate this correlation using additional subjects and examined the function of Garem1 in a mouse model. We analyzed the association of rs17744182, a variant in the GAREM1 locus, with the PR interval in 5646 subjects who were recruited from 2 Korean replication sets, Yangpyeong (n = 2471) and Yonsei (n = 3175), and noted a significant genomewide association by meta-analysis (P = 2.39 × 10 ). To confirm the function of Garem1 in mice, Garem1 siRNA was injected into mouse tail veins to reduce the expression of Garem1. Garem1 transcript levels declined by 53% in the atrium of the heart (P = 0.029), and Garem1-siRNA injected mice experienced a significant decrease in PR interval (43.27 ms vs. 44.89 ms in control, P = 0.007). We analyzed the expression pattern of Garem1 in the heart by immunohistology and observed specific expression of Garem1 in intracardiac ganglia. Garem1 was expressed in most neurons of the ganglion, including cholinergic and adrenergic cells. We have provided evidence that GAREM1 is involved in the PR interval of ECGs. These findings increase our understanding of the regulatory signals of heart rhythm through intracardiac ganglia of the autonomic nervous system and can be used to guide the development of a therapeutic target for heart conditions, such as atrial fibrillation.